Ernest Everett Just: Egg and embryo as excitable systems. Issue 4 (24th March 2014) - Byrnes, W. Malcolm; Newman, Stuart A.
ABSTRACT Ernest Everett Just (1883–1941) was an African American embryologist of international standing whose research interests lay in the area of fertilization and early development in marine invertebrates. Perhaps best known for his discovery of the dynamical and structural blocks to polyspermy that sweep over the egg upon fertilization, E. E. Just also was the first to associate cell surface changes with stages of embryonic development. He was deeply familiar with the natural history of the animals whose eggs he studied, and his knowledge of natural settings led him to emphasize the importance of using laboratory conditions that closely match those in nature. Based on more than 30 years of work, he came to believe that it was the cell surface that played the most critical role in development, heredity, and evolution. He promoted a holistic view of cells and organisms in opposition to the gene‐centric view that was becoming more prevalent with the rise of genetics, but rejected the vitalism espoused by some biologists of his era, calling instead for "a physics and chemistry in a new dimension …superimposed upon the now known physics and chemistry" to account for biological phenomena. Just's incisive critique of genetic reductionism finds echoes in contemporary multiscale, systems approaches in biology. His speculations on the relationship between developmental and evolutionary mechanisms resonate with today's evolutionary developmental biology. After a brief biographical sketch, this paper outlines and discusses some of Just's scientific contributions, and shows how his ideas remain relevant today. J. Exp. Zool. (Mol. Dev. Evol.) 322B: 191–201, 2014. © 2014 Wiley Periodicals, Inc.